The Flash. Vol. 11, The greatest trick of all - Williamson, Joshua (DC Comics, 2020)
After the death of a friend and the end of his relationship with Iris West, Barry Allen returns to Central City and finds things have mysteriously changed. Then the Flash's ally from the future, Commander Cold, disappears. While the Flash is investigating a connection to Iron Heights Prison, the original Trickster James Jesse, a member of Flash's Rogues Gallery, sets a plan into motion.